Locul și rolul medicilor veterinari specialiști Români in contextul reglementarilor CMVRO – AGMV – MEC - Nistor Maierean (Medicamentul Veterinar)
In this PPT, a presentation is made about the importance of the veterinarian as a specialist, in the context of the national regulations, from the National Register of Qualifications in Higher Education, the College and the General Association of Veterinary Doctors in Romania and about the training, specializations and professional promotion existing in our country the country. In the second part, useful information is presented about the qualifications offered by the European Board of Veterinary Specializations (EBVS), which can grant the title of "European Veterinary Specialist", in various fields (including ECVPT -European College of Veterinary Pharmacology and Toxicology). Finally, the list of occupational fields in which specialist veterinarians could practice in Romania is presented.